Danish arctic expeditions, 1605 to 1620 [electronic resource] : in two books - Hall, James, d. 1612.; Gosch, C. C. A. (Christian Carl August), 1832-1913.; Gatonbe, John.; Christy, Miller, 1861-1928.; Baffin, William, 1584-1622. (London : Printed for the Hakluyt Society, 1897)
Part of a CIHM set. For individual microfiches in this set see CIHM microfiche nos. 08550-08552. Original issued in series: Works issued by the Hakluyt Society no. 96. "Book I. : The Danish expeditions to Greenland in 1605, 1606, and 1607 to which is added Captain James Hall's voyage to Greenland in 1612." Includes index. Includes bibliographical references. Electronic reproduction. Mode of access: Internet. 44